IgG4-mediated M2 macrophage polarization in tertiary lymphoid structures of esophageal cancer: implications for immunosuppression - Wang, Hui; Li, Jirui; Wang, Yinghai; Chen, Yang; Zhang, Weifeng; Pan, Xinyan; Su, Chanjuan; Li, Ziteng; Wang, Li; Gu, Jiang (Frontiers in Immunology, 2025)
BackgroundOur previous research highlighted the potential role of immunoglobulin G4 (IgG4) in mediating immunosuppression within the tumor microenvironment (TME). Tertiary lymphoid structures (TLS) in the TME have important immune-related functions. This study aims to analyze the distribution characteristics of IgG4-expressing cells, regulatory T cells (Tregs), and M2-type macrophages as well as to elucidate the relationship between IgG4 and the polarization of M2 macrophages within TLS in esophageal cancer.ObjectTo elucidate the distribution of IgG4, Treg cells, and M2 macrophages in TLS and to assess the impact of IgG4 on macrophage polarization.MethodsEsophageal cancer tissue were analyzed with multiplex immunofluorescence to determine the spatial distribution and density of B cells, T cells, and their subtypes. The relationship between IgG4 and CD8+ T cells in TLS, along with interleukin-10 (IL-10) expression and Treg presence, was studied. Serum IgG4 and IL-10 levels were compared between patients and healthy controls. In vitro, the impact of IgG4 on monocyte differentiation into M2 macrophages was observed.ResultsIgG4 density was inversely related with CD8+ T cells in mature TLS indicating a potential immunosuppressive role (P<0.05,*). Serum analysis revealed that both IgG4 (P<0.01, **) and IL-10 (P<0.0001, ****) were significantly elevated and positively correlated in tumor patients compared to controls (P<0.01, **). In vitro experiments confirmed that IgG4 monocyte differentiation into M2 macrophages, potentially enhancing the immunosuppressive phenotype in TLS.ConclusionIgG4 and IL-10 may contribute to immunosuppression in esophageal cancer by promoting the polarization of M2 macrophages within TLS, which could be a therapeutic target.